Softwood grafting is a boon to mango growers - Dubey, A K; Srivastav, Manish; Kundu, Manoj (Indian Horticulture, 2019)
Introduction: The soft wood grafting in mango can be done for a longer period starting from April to August. The plants are ready for planting 4-5 months after grafting. The technique is quite easy. In North India, plants are ready from April to August. It would be a boon to mango orchardists.